Efeito fitotóxico e potencial remediador de três espécies vegetais contaminadas com benzeno - Medeiros, Thales Augusto de Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The environment most directly affected by human contamination is the soil and consequently groundwater. In phytoremediation process, the direct absorption of contaminants in the soil by the roots, prevents contamination of groundwater or to reduce the size of the plume, protecting receptor sites. The aim of this study was to evaluate the remedial potential and the indicator responses disorders of three plant species when exposed to benzene. The species used were a monocotyledon (Brachiaria brizantha (A. Rich.) Stapf), a eudicotyledon (Impatiens walleriana Hook. F.) and a fern (Pteris vittata L.). To assess the potential remedial were made direct injection testes and benzene mist on the species. Pteris vittata showed low absorption (5.88%) and accumulated mainly in the root, which was also observed by the absence of visual symptoms of phytotoxicity. Impatiens walleriana showed high removal rates of benzene and after suspension of the contamination, the species reacted to the detoxification process and regained stem stiffness and color of the leaves. Brachiaria brizantha did not react to the detoxification process and the end of treatment died. To understand the indicator responses disorders the leaves were removed, processed and fixed according to standard techniques for analysis in a scanning electron microscope to identify changes in the surface of the leaves. The three species showed an increase in stomatal density, after the treatment with benzene injection. The hydrogen peroxide accumulation and cell death indication are responses to the presence of benzene in the leaves. In benzene contamination by mist, the three species showed phytotoxic effects, such as changes in stomatal density and stomatal size. At the end, we have the Impatiens walleriana as a species, which adds more features desirable to phytotechnology. Pteris vittata and B. brizantha don’t showed phytoremediation potential ...

O meio mais diretamente afetado pela contaminação antrópica é o solo e, consequentemente, a água subterrânea. No processo de fitorremediação, a absorção direta de contaminantes no solo, através das raízes, evita a contaminação da zona freática, ou mesmo, pode reduzir o tamanho da pluma de contaminação de benzeno, protegendo os pontos receptores. O objetivo do estudo foi avaliar o potencial remediador e as respostas indicadoras de distúrbios de três espécies vegetais, quando expostas ao benzeno. Entre a espécies estudadas tem-se uma monodicotiledônea (Brachiaria brizantha), uma eudicotiledônea (Impatiens walleriana) e uma samambaia (Pteris vittata). Para avaliar o potencial remediador foram efetuados ensaios de injeção direta e nebulização de benzeno sobre as espécies. Pteris vittata apresentou baixa absorção (5,88%) e acumulou principalmente na raiz, o que também foi observado através da ausência de sintomas visuais de fitotoxicidade. Impatiens walleriana apresentou altas taxas de remoção de benzeno e após a suspensão da contaminação, a espécie reagiu ao processo de desintoxicação, recuperando a rigidez do caule e coloração das folhas. Brachiaria brizantha não reagiu ao processo de desintoxicação e morreu ao final do tratamento. Para compreender as respostas indicadoras de distúrbios, as folhas foram retiradas, processadas e fixadas segundo técnicas usuais, para análise em microscopia eletrônica de varredura, para identificar injúrias microscópicas na superfície foliar. As três espécies vegetais apresentaram aumento na densidade estomática, posteriormente ao tratamento com injeção de benzeno. O acúmulo de peróxido de hidrogênio e a indicação de morte celular foram respostas à presença do benzeno nos tecidos foliares. Na nebulização com o contaminante, as três espécies apresentaram efeitos fitotóxicos, como alteração na densidade estomática e tamanho dos estômatos ...
Keywords: Benzeno; Fitorremediação; Plantas; Stress oxidativo; Meio ambiente – Contaminação